Corporate social responsibility and greenwashing in a banana exporting company - Ruiz Espinoza, Ashly Britany Shantal; Cosio Borda, Ricardo Fernando; Ramírez Briones, Lorena; Cajavilca Gonzáles, Berenice; Buitron Hurtado, Erika del Rosario; Reyes Carhuapoma, Tamara Sheyla (LACCEI, 2024)
The objective of the research was to examine the relationship between corporate social responsibility (CSR) and greenwashing in a banana exporting company in Sullana during the year 2023, with an approach focused on the perspective of the workers. A cross-sectional non-experimental quantitative design was used with a correlational approach, applying a questionnaire to 29 company workers, using a 5-point Likert scale. The results revealed a moderate and statistically significant negative correlation between the CSR and greenwashing variables, represented by a correlation coefficient of -.665 and a significance level of .001. These findings indicated that, as corporate social responsibility activities increased, greenwashing decreased in the company and vice versa, although this variation was not proportional. The research highlights the importance of considering the perspective of workers when analyzing the relationship between CSR and greenwashing.